The Metalworker and his Tools: QUB Belfast Conference - E. Giovanna Fregni (EXARC Journal, 2016)
A recent conference, funded partially by UISPP, was held in Queens University Belfast. While its main focus was on Bronze Age metalsmithing tools and assemblages, the MeTools conference (23-25 June at Queen’s University, Belfast) had several presentations that focussed on experimental archaeology as a means of exploring metalworking craft.